2017
DOI: 10.14738/abr.510.3652
|View full text |Cite
|
Sign up to set email alerts
|

Riding the Waves of Technology: A Study into How SMEs Select Computerized Accounting Software (CAS) supplier in Developing Countries

Abstract: Many SMEs are foreseeing the immense benefits of implementing CAS to facilitate the processing of their financial reporting. This Phenomenon has led to the spread of many CAS products in the software market, making it difficult to select the best among them for implementation. The sub-optimality of CAS is as a result of functionalities such as Scalability ;Capacity; Ease of Data Input ; Security; Speed of Installation ; CAS Consultant/Vendor ; Reporting Capabilities ; Error Handling ; Audit Trail ;Data Validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Çalışma sonucunda muhasebe uzmanları için en önemli kriterin güvenlik olduğu bulgusuna ulaşılmıştır. Aduamoah (2017) çalışmasında GANA'da faaliyet gösteren KOBİ'lerin muhasebe paket programı tercihini etkileyen faktörleri tespit etmeye çalışmıştır. Çalışma sonucunda KOBİ'lerin ihtiyaçları doğrultusunda farklı modülleri içeren, özelleştirilebilir programların tercih edildiği, bu konuda satıcı desteğinin de oldukça önemli olduğu sonucuna ulaşmıştır.…”
Section: Literatür Taramasıunclassified
“…Çalışma sonucunda muhasebe uzmanları için en önemli kriterin güvenlik olduğu bulgusuna ulaşılmıştır. Aduamoah (2017) çalışmasında GANA'da faaliyet gösteren KOBİ'lerin muhasebe paket programı tercihini etkileyen faktörleri tespit etmeye çalışmıştır. Çalışma sonucunda KOBİ'lerin ihtiyaçları doğrultusunda farklı modülleri içeren, özelleştirilebilir programların tercih edildiği, bu konuda satıcı desteğinin de oldukça önemli olduğu sonucuna ulaşmıştır.…”
Section: Literatür Taramasıunclassified
“…Scholars Broy M., Kruger I.H., and Pretschner A. clearly described the essence of automotive software, and discussed the selection and rating of Automotive Software Engineering [8]. Aduamoah M. carried out research on how small and medium-sized enterprises in developing countries choose computer accounting software suppliers [9]. Fabbrini F., Fusani M., and Lami G. took the results of software process (ISO/IEC15504) evaluation as one of the requirements for software companies to obtain software orders [10].…”
Section: Literature Overviewmentioning
confidence: 99%
“…Research findings have also showed some major problems faced by SMEs are incomplete records, lack in control of finance, staff inexperience, poor power supply, and such others (Ogundana, Okere, Ayomoto, Adesanmi, Ibidunni & Ogunleye, 2017). Wrong selection of accounting software for a company may leads to financial losses, bankruptcies of the company, closure of the company and losses of jobs to accounting personnel (Aduamoah, 2017). The adoption of computerized accounting system leads to accountants who can use specific software and thus costs more (Taiwo, 2016).…”
Section: Introductionmentioning
confidence: 99%